Spectrum of cutaneous manifestations in patients with type 2 diabetes mellitus - Roby Bose; Sunil Kumar (Asian Journal of Medical Sciences)
Background: Skin disorders, usually neglected and frequently under diagnosed among diabetic patients. These are common complications and encounter a broad spectrum of disorders in diabetes.